Hsp70 Gene Polymorphisms Are Associated With Disease Susceptibility and HRQOL Improvement in Chinese Han Population With Systemic Lupus Erythematosus. Issue 4 (June 2020) - Xie, Qiao-Mei; Lou, Qiu-Yue; Huang, Shun-Wei; Hu, Hua-Qing; Li, Su-Su; Zhang, Man; Sun, Xiu-Xiu; Xu, Jian-Hua; Jiang, Shan-Qun; Liu, Sheng-Xiu; Xu, Sheng-Qian; Cai, Jing; et al.
Abstract : Objectives: The aim of this study is to investigate whether heat shock protein 70 (Hsp70) gene polymorphisms are implicated in systemic lupus erythematous (SLE) susceptibility, the efficacy of glucocorticoids (GCs) treatment, and improvement of health-related quality of life. Methods: A total of 499 SLE patients and 499 controls were included in a case-control study, and 468 SLE patients treated with GCs for 12 weeks were involved in a follow-up study. Patients who completed the 12-week follow-up were divided into GCs-sensitive and GCs-insensitive group by using the SLE disease activity index. The SF-36 was used to evaluate the health-related quality of life of SLE patients, and genotyping was performed by improved multiplex ligation detection reaction. Results: rs2075800 was associated with SLE susceptibility (adjusted odds ratio [ORadj ], 1.437; 95% confidence interval [CI], 1.113–1.855; P adj = 0.005; P BH = 0.020 by dominant model; ORadj, 1.602; 95% CI, 1.072–2.395; P adj = 0.022; P BH = 0.029 by TT vs CC model; ORadj = 1.396; 95% CI = 1.067–1.826; P adj = 0.015; P BH = 0.029 by TC vs CC model). In the follow-up study, rs2075799 was associated with the improvement in mental health ( p = 0.004, P BH = 0.044), but we failed to find any association between the efficacy of GCs and Hsp70 gene polymorphisms. Conclusions: Hsp70 gene polymorphisms may be associated with susceptibility to SLE and improvement of mental health in Chinese Han population. Abstract : Supplemental digital content is available in the text. This is a case control study of nearly 500 lupus patients and 500 controls who were genotyped for Hsp70 gene polymorphisms by multiplex ligation detection reaction. Although there was an association between rs2075800 polymorphism and lupus, no relationship with disease activity or with the use of steroids was found. On the other hand, rs2075799 was associated with a better mental health as assessed by the SF-36.